Model Promosi Kesehatan Bidan Pada Ibu Hamil Pre Eklamsi Berdasarkan Stage Of Change (Kajian Transtheory Model) - Jamhariyah, Jamhariyah; Sugijati, Sugijati; Prijatni, Ida (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2020)
Complications that need to occur in pregnant women and need to be done is preeclampsia. From 2012 to 2016, pre-eclampsia was ranked as the first cause of AKI in East Java, the case of preeclampsia in 2016 was 30.90% (1). In Jember in 2015 there were 31 cases of preeclampsia deaths. Data from the Ajung Puskesmas (2017) were 45 preeclampsia cases from January to September. A preliminary study of 10 preeclampsia TM III pregnant women, using a structured interview method, obtained 6 mothers undergoing routine checks with a record of 3 mothers achieving success but not yet performing optimally. The purpose of this research is to make a model of health promotion for midwives in pregnant women with Trimester III preeclampsia based on the Change Phase. The design of this study is quasi-experimental. Sampling using simple random sampling technique totaling 75 respondents. R&D research. Instrument questionnaire sheet. Obtained differences after being given bidkes based on the stage of change. Statistical test analysis with the value of Pre Conteplation Z count (-7,022)> Z Table 0.05 (1.96) so that Ho is rejected, the value of Pre Conteplation is increasing, Hi Conteplation Z count (-6,244)> Z Table 0.05 (1 , 96) so that it can quickly increase the value of increased conteplation. Preparation Stage Calculated Z values ??(-7,253)> Z Table 0.05 (1.96) Ho is rejected the value of increasing contemplation. Action stage Z count (-6,304)> Z Table 0.05 (1.96) so that Ho is rejected the value of Conteplation increases. Changing the behavior of preeclampsia requires a health promotion model that is informed according to policy level. Keywords: Preeclampsia Pregnant Women, Promotion Model, Stage of Change